A Putative Role for the Immunoproteasome in the Maintenance of Pluripotency in Human Embryonic Stem Cells123. (18th June 2012) - Atkinson, Stuart P.; Collin, Joseph; Irina, Neganova; Anyfantis, George; Kyung, Bo Kim; Lako, Majlinda; Armstrong, Lyle
Abstract: The function of the proteasome is essential for maintenance of cellular homeostasis, and in pluripotent stem cells, this has been extended to the removal of nascent proteins in a manner that restricts differentiation. In this study, we show enhanced expression of genes encoding subunits of the 20S proteasome in human embryonic stem cells (hESCs) coupled to their downregulation as the cells progress into differentiation. The decrease in expression is particularly marked for the alternative catalytic subunits of the 20S proteasome variant known as the immunoproteasome indicating the possibility of a hitherto unknown function for this proteasome variant in pluripotent cells. The immunoproteasome is normally associated with antigen‐presenting cells where it provides peptides of an appropriate length for antibody generation; however, our data suggest that it may be involved in maintaining the pluripotency in hESCs. Selective inhibition of two immunoproteasome subunits (PSMB9 and PSMB8) results in downregulation of cell surface and transcriptional markers that characterize the pluripotent state, subtle cell accumulation in G1 at the expense of S‐phase, and upregulation of various markers characterizing the differentiated primitive and definitive lineages arising from hESC. Our data also support a different function for each of these two subunits in hESC that may be linked to their selectivity in driving proteasome‐mediated degradation of cell cycle regulatory components and/or differentiation inducing factors. STEM Cells 2012;30:1373–1384